Classification of the Second Minimal Orbits in the Sharkovski Ordering - Ugur G. Abdulla; Naveed H. Iqbal; Muhammad U. Abdulla; Rashad U. Abdulla (Axioms)
We prove a conjecture on the second minimal odd periodic orbits with respect to Sharkovski ordering for the continuous endomorphisms on the real line. A <semantics>(2k+1)</semantics>-periodic orbit <semantics>{β1<β2<⋯<β2k+1}</semantics>, (<semantics>k≥3</semantics>) is called second minimal for the map f, if <semantics>2k−1</semantics> is a minimal period of <semantics>f|[β1,β2k+1]</semantics> in the Sharkovski ordering. Full classification of second minimal orbits is presented in terms of cyclic permutations and directed graphs of transitions. It is proved that second minimal odd orbits either have a Stefan-type structure like minimal odd orbits or one of the <semantics>4k−3</semantics> types, each characterized with unique cyclic permutations and directed graphs of transitions with an accuracy up to the inverses. The new concept of second minimal orbits and its classification have an important application towards an understanding of the universal structure of the distribution of the periodic windows in the bifurcation diagram generated by the chaotic dynamics of nonlinear maps on the interval.